2018
DOI: 10.1177/0734242x18804041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chicken feather and boron compounds as filler on mechanical and flame retardancy properties of polymer composite materials

Abstract: Sustainable utilisation of solid waste has been influenced by the increasing population of the world. Benefits of using solid waste based on natural fibre in polymer material are biodegradability and cost effectiveness. In poultry farms, chicken poultry, one of the slaughterhouse wastes is confronted with 30 106 kg of waste per year in Turkey. The evaluation of this waste, which is quite rich in keratin, is extremely important both for the solution of the waste problem and for maintaining a clean environment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
(18 reference statements)
0
11
0
1
Order By: Relevance
“…7,10 The addition of boron compounds into polymer matrices has received much interest in recent years as they improve mechanical properties, thermal stability, and especially flame retardancy compared with the pure polymer. [16][17][18] Boron compounds have a rather low melting point and form glassy films when exposed to fires. By means of this film barrier, combustible volatiles cannot proceed to the fire exposed surface.…”
Section: Introductionmentioning
confidence: 99%
“…7,10 The addition of boron compounds into polymer matrices has received much interest in recent years as they improve mechanical properties, thermal stability, and especially flame retardancy compared with the pure polymer. [16][17][18] Boron compounds have a rather low melting point and form glassy films when exposed to fires. By means of this film barrier, combustible volatiles cannot proceed to the fire exposed surface.…”
Section: Introductionmentioning
confidence: 99%
“…34 It was found the presence of the CFF in the polymer matrix gave rise to the reduction in the density of the produced composites as well as the formation of the synergetic (dual) reinforcement effect when it was used with the glass fiber. Similarly, the role of the chicken feather and boron compounds on the mechanical and flame retardancy features of polymer composite were examined in the study done by Kuru et al 35 Furthermore, in one of the foregone study, Gokce et al 36 investigated the preparation, characterization, and potential usage of the chicken feather fiber–thermoplastic polyurethane (CFF–TPU) composites as tissue engineering scaffolds. They revealed that the prepared composite containing 40% of CFF depicted the larger improved modulus and strength (28.7 MPa) compared to both neat TPU and other composites produced.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there existed many studies in literature corresponding to the boron mineral which were utilized as a filler in the polymer composites in order to impart the advanced characteristics such as mechanical, flame retardancy, water absorption etc. to the polymers [27][28][29][30]. Furthermore, boron minerals make the scientists unable to fabricate halogen free polymer composite by means of their flame retardant characteristic feature [31,32].…”
Section: Introductionmentioning
confidence: 99%